Hepatic paragonimiasis in a 15-month-old girl: a case report - Zongrong Gong; Zhicheng Xu; Chuanfen Lei; Chaomin Wan (BMC, 2017)
Abstract Background Paragonimiasis, particularly hepatic paragonimiasis (HP), is a type of zoonotic parasitic disease rarely encountered in infants. There have been only a few reports of HP, and no case of HP has been reported in an infant. Case presentation A 15-month-old girl presented with persistent mild fever with a duration of 1 month, hepatomegaly, and low-density lesions in the right hepatic lobe on abdominal ultrasound and computer tomography. Pathological examination and serum antibody detection were performed to verify HP. The diagnosis of HP was established based on findings of Charcot-Leyden crystals on liver lesion biopsy and antibodies against paragonimus westermani detected by enzyme-linked immunosorbent assay. After initiation of praziquantel (75 mg/kg/day for 3 days), all clinical findings promptly improved and the patient was discharged. Conclusion It is very important to consider paragonimiasis in the clinical examination of infants from an area with paragonimiasis epidemic presenting with fever, hepatomegaly, low-density lesions in the liver.